Bad Friends Make Bad Boys? The Mediating Effects of Gender-Role Stereotypes on the Relationship Between Delinquent Peer Association and Violent Behavior Adolescents Boys - Lee, Wonki (Criminal justice and behavior, 2025)
Although the link between delinquent peer association and violent behavior in adolescent boys is well documented, the underlying mechanisms are less explored. To address this gap, this study examines the mediating role of gender-role stereotypes in the relationship between delinquent peer association and violent behavior. Structural equation modeling was conducted using a longitudinal, nationally representative sample of South Korean adolescents (N = 1,444). Results indicate that delinquent peer association is a significant source of the development of gender-role stereotypes in adolescent boys. Furthermore, these gender-role stereotypes, influenced by delinquent peer association, significantly increase the likelihood of engaging in violent behavior. Overall, the study reveals that gender-role stereotypes partially mediate the effect of delinquent peer association on violent behavior.